Land Cover Change Analysis Around the Sundarbans Mangrove Forest of Bangladesh using Remote Sensing and GIS Application - Rahman, MR; Begum, S (Journal of Science Foundation, 2013)
Land cover change is a widespread and prominent feature in Bangladesh. It is more energetic in the South-west coastal region such as Khulna and Satkhira region. The research was completed by 30 years (1980 to 2009) by using four Landsat satellite images (1980, 1989, 2002 and 2009). During research it was originated that the main classes of changes were homestead, fallow land, water bodies and mangrove vegetation in the study area. The most imperative change was observed in fallow lands (the types of cultivable lands with or without any standing crops and also uncultivable lands). Fallow land was decreased, concerning 2,259 sq km in 2009 which land was 3,867 sq km during in 1980. It was dropped 49% to 29% of total study area between the years of 1980 to 2009. The water bodies were increased about 10% in those 30 years, regarding 14% to 24%. The total water bodies covered 1140 sq km at 1980 which was increased 1851 sq km during 2009 in the study area. The sea-level rise, increasing salinity and availability of less fresh water are responsible for inland intrusion of saline water and creating favorable environment for shrimp farming in the region. As a result farmers are converting fallow lands to shrimp farming which is economically very beneficial. Important agricultural and non-agricultural lands also converted by homestead intended for increasing population of Bangladesh. There was only 398 sq km (only 5%) area covered by homestead during 1980. But the homestead covered area was increased about 1490 sq km (19%) at 2009. So, compared to the last 30 years 14% homesteads land cover areas are increased. There was not any astonishing changed in mangrove vegetation. Some mangroves areas were shattered and some other mangroves were full-fledged again in delta areas. The harmful land cover changes are not expectable for the natural environment. But it transpires by many natural and anthropogenic tricks now a day. So, the authority should seize initiatives to protect this category of catastrophe. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14652 J. Sci. Foundation, 9(1&2): 95-107, June-December 2011